Eksplorasi Aktivitas Daun Pegangan (Centella Asiatica) dalam Mempercepat Proses Penyembuhan Luka - Teuku Daffa Hasian; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Various therapeutic strategies have been developed to promote effective and safe wound healing, particularly those derived from natural sources. Centella asiatica has gained significant attention due to its bioactive compounds that support skin tissue regeneration. This paper aims to comprehensively review the biological activity and pharmacological mechanisms of Centella asiatica in the wound healing process. The study employed a qualitative descriptive method using a literature review approach, analyzing relevant national and international scientific publications. The findings indicate that major triterpenoid compounds, including asiaticoside, madecassoside, asiatic acid, and madecassic acid, play essential roles in stimulating fibroblast proliferation, enhancing collagen synthesis, accelerating epithelialization, and regulating inflammation and oxidative stress. In addition, the antibacterial properties and pigmentation-modulating effects of Centella asiatica contribute to improved wound healing quality. The use of modern topical formulations has been shown to increase bioavailability and therapeutic efficacy. In conclusion, Centella asiatica demonstrates strong potential as a safe, effective, and applicable natural-based therapeutic agent for wound management and dermatological application